LASER correction of malarphyma & a brief review of literature. (March 2017) - Arnaout, Ali; Dobbs, Thomas; Yarrow, Jeremy; Logan, Richard; Murison, M.S.C.
Abstract: Introduction: We present a rare manifestation of phymatous change normally confined to the nose and anterior cheeks, which in our case had malar involvement and little in the way of nasal involvement. We have coined the term Malarphyma to describe this condition. Malarphyma is a condition of the skin of the cheeks, which is related to the more commonly presented rhinophyma. It does not have a specific underlying aetiology but is possibly linked to chronic, severe rosacea. Malarphyma is progressive, with early clinical findings including enlarged pores, thickening of the fibrous tissue and hypertrophy of the sebaceous glands. Both rhinophyma and malarphyma can lead to debilitating functional and psychosocial problems for patients affect by it. Results: We describe for the first time in the literature the use of the CO2 LASER for the management of malarphyma and review the literature pertaining to the use of LASER to treat rhinophyma and the associated malarphyma using a PRISMA 2009 checklist approach to identify eligible studies. Discussion: The management of rhinophyma and associated conditions have developed over time. Medical treatment with oral antibiotics or isotretinoin is possible, but the successful treatment of established rhinophyma more commonly requires some form of surgical treatment. CO2 LASER is recognised as the gold standard for soft tissue vaporization, with multiple reported favourable outcomes the treatment of rhinophyma, with excellent cosmetic results and patient satisfaction. Conclusion: CO2 LASER is an effective method of tissue ablation with an excellent safety profile, as proven throughout the medical literature over a number of years, but no single method that is free of complications and no well designed studies demonstrate significant benefits of one method over another. We acknowledge that the outcome and complications associated with CO2 LASER depends on the clinician's experience with LASER treatment, in the correctly selected patient.